Kegiatan bercerita dan mewarnai gambar pada anak usia dini sebagai bentuk penanaman karakter toleransi beragama di desa Kedawung Jumapolo Karanganyar - Muin Abdullah; Nur Hidayah; Oxsyana Ayuk Mustarofah (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2023)
This activity was carried out in a Kedawung village, Jumapolo District, Karanganyar Regency. Kedawung Village is one of the villages in the Jumapolo sub-district, and the occupation is mostly non-Muslims; therefore, instilling the character of religious tolerance is very important so children with different religious backgrounds can respect each other. So that it will create harmony and unity in everyday life in society. This community service activity in Kedawung village uses storytelling and hands-on practice. By using this storytelling method, one can find out how effective the storytelling technique is in increasing the development of tolerance values ​​in students. The results of the implementation of community service in the form of stimulating children to color and tell stories that have been carried out can increase children’s tolerance, such as children being able to work together in completing coloring assignments because they consider that they are the same. There are no differences between them. The students can internalize and understand the religious values wholeheartedly without having to use coercion from anywhere so that the religious values ​​taught can always be applied in their lives. This shows that by telling stories and coloring, the character of religious tolerance can be successfully instilled in children.